Investigation of a linezolid-resistant Staphylococcus epidermidis outbreak in a French hospital: phenotypic, genotypic, and clinical characterization - Lépine, Nadège; Bras-Cachinho, José; Couratin, Eva; Lemaire, Coralie; Chaufour, Laura; Junchat, Armelle; Lartigue, Marie-Frédérique (Frontiers in Microbiology, 2024)
We aimed to retrospectively investigate an outbreak of linezolid-resistant Staphylococcus epidermidis (LRSE), at Tours University Hospital between 2017 and 2021.Methods: Twenty of the 34 LRSE isolates were included in the study. Antimicrobial susceptibility testing was performed using the disk diffusion method and MICs of last-resort antibiotics were determined using broth microdilution or Etest. Seventeen of the 20 resistant strains were sent to the French National Reference Centre for Staphylococci to determine the mechanism of resistance to linezolid. The clonal relationship between LRSE strains was assessed by PFGE and the sequence type determined by MLST. We retrospectively evaluated a new typing tool, IR-biotyper, and compared its results to PFGE to evaluate its relevance for S. epidermidis typing. Medical records were reviewed, and antibiotic consumption was determined. Search for a cross transmission was performed. Results: All LRSE strains showed high levels of resistance to linezolid (MICs ≥ 256 mg/L) and were multi-drug resistant. Linezolid resistance was associated with the 23S rRNA G2576T mutation and none of the 17 strains analyzed carried the cfr gene. Ninety-five percent of the 20 LRSE studied strains were genetically related and belonged to sequence-type ST2. The dendrogram obtained from IR-Biotyper showed 87% congruence with the PFGE analysis. Prior to isolation of the LRSE strain, 70% of patients received linezolid. No patients stayed successively in the same room.Linezolid exposure may promote the survival and spread of LRSE strains. At Tours University Hospital, acquisition of the resistant clone may also have been triggered by hand-to-hand transmission by healthcare workers. In addition, IR-biotyper is a promising typing tool for the study of clonal outbreaks due to its low cost and short turnaround time, although further studies are needed to assess the optimal analytical parameters for routine use.